Arginine vasotocin is a player in the multifactorial control of spermatogenesis in zebrafish - Zanardini, Maya; Parker, Nicolas; Ma, Yifei; Habibi, Hamid R. (Frontiers in Endocrinology, 2025)
This study investigated the role of vasotocin (AVT) in the multifaceted regulation of spermatogenesis in zebrafish, with a focus on its interaction with gonadotropin hormones. Using an ex vivo cultured testis, we explored the interaction of AVT with gonadotropins, LH and FSH, to regulate different stages of germ cell development. In this study, we used recombinant zebrafish FSH and hCG to stimulate the LH-induced response due to the limited availability of zebrafish LH, as it is known to exert similar effects on testicular function. Treatment with AVT enhanced FSH-induced proliferation of early undifferentiated spermatogonia (Aund) germ cells, as well as promoting the proliferation of later-stage type B germ cells when combined with LH/hCG. Additionally, AVT significantly decreased FSH-induced 11-ketotestosterone (11-KT) production and Leydig-derived factors, including cyp17a1 and insl3, without significantly affecting LH/hCG-induced androgen production. Based on these findings, we hypothesize that in the presence of FSH, AVT drives early germ cell proliferation and differentiation while simultaneously inhibiting premature progression through spermiogenesis. This stage-specific modulation of gonadotropin signaling by AVT underscores its dual role in fine-tuning testicular function and germ cell maturation in male zebrafish. Overall, our findings suggest that AVT contributes to the complex multifactorial network regulating spermatogenesis in zebrafish.